Navigating the Same Storm but Not in the Same Boat: Mental Health Vulnerability and Coping in Women University Students During the First COVID-19 Lockdown in the UK - Misca, Gabriela; Thornton, Gemma (Frontiers in Psychology, 2021)
Having a mental health diagnosis in both general and student populations has been found to be a risk factor for negative coping and increased psychological distress during the COVID-19 pandemic. Drawing on a subset of data from a large contemporaneous research study, this report explores the experiences of 36 women students with and without reported pre-existing mental health diagnoses during the first UK lockdown, in spring 2020. Specifically, the data explored self-reported coping with the restrictions, with the abrupt move to online learning, and the loss of support; as well as students’ perceived strengths and difficulties in balancing their student role with family roles such as being a partner and/or a parent. Students with a pre-existing mental health diagnosis reported higher levels of loneliness compared to a matched sample of non-students, and more avoidant coping and negative emotional coping than students without a diagnosis. Qualitative data illustrate how parenting intersects with wellbeing and stress as both a protective and risk factor for women university students. This research report adds to the evidence base on the impact of the COVID-19 pandemic on the student population, and how pre-existing mental health diagnoses intersect with coping behaviours and vulnerability in women students. Exploration of potential vulnerabilities can provide opportunities for targeted support, and identifying effective coping has the potential to inform effective interventions.